Indian power distribution sector reforms: A critical review. (September 2020) - Verma, Mandhir Kumar; Mukherjee, V.; Kumar Yadav, Vinod; Ghosh, Santosh
Abstract: For expansion of any country's economy, development of infrastructure, and eventually improving the quality of life, electrical power is one of the greatest enabler. And hence three decades back, India, initiated power sector reforms to make its power sector efficient and sustainable. However, even three decades after starting the reform initiatives, almost all the state power utilities are under significant financial and technical losses, which is hindering further expansion and strengthening of distribution system. This paper analyses the present scenario of Indian power distribution sector and the reasons behind it's poor financial and technical performance. Through the comprehensive analysis, it is shown that even after introduction of new policies, reforms, and regulatory initiatives, Indian distribution sector is still suffering from systemic flaws and vulnerabilities characterized by cross-subsidies, inefficiency, substantial technical and financial losses, poor quality of power, low efficiency, outstanding debts, frequent supply disruptions, inability of expansion, sluggish privatization, poor customer satisfaction, political interference, and low reliability. This paper discusses the chronology of reforms brought in so far in the power distribution sector in India, and further suggests measures that can be adopted in administrative, technical, and commercial fields to improve the quality and reliability of supplied power. Highlights: Presents comprehensive analyse of Indian power distribution sector scenario. Chronology of reforms introduced so far in the power distribution sector in India. Reasons behind financial un-sustainability of power utilities are analysed. Required policy interventions are suggested for improving the performance.